PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT DALAM MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TKIT KHALIFAH - Maulina Rahayu; Amat Hidayat (Jurnal Anak Bangsa, 2023)
Learning in early childhood requires innovative learning media to optimize its development, especially in the language aspect. The use of media in learning is considered effective and can create a pleasant learning atmosphere so as to increase children's interest in learning. This study aims to develop interactive learning multimedia, determine the feasibility, effectiveness, and responses of students to interactive learning multimedia. This type of research is the development research (R&D) of the ADDIE reference model. Methods of data collection using observation, questionnaires, and documentation. Data were obtained from media experts, material experts, field practitioners and students. The instruments used are questionnaires and observation sheets. The data analysis technique used is qualitative and quantitative analysis. Research results: The validity test according to media experts, material experts and field practitioners obtained an average score of 87.4% with very good qualifications. The effectiveness of the control and experimental class post-test scores with sig 0.000 <0.05, there is a difference between the control and experimental class post-test results and the student response of 85.1% with very good qualifications. Based on the results of the research that the development of interactive learning multimedia is very feasible to use in the language aspect, especially the speaking ability of early childhood. The implication of this research is that this interactive learning multimedia product can be a solution to existing problems, which can be used in learning to stimulate the speaking ability of children aged 5-6 years and can make learning more varied.